2004
DOI: 10.1099/mic.0.26826-0
|View full text |Cite
|
Sign up to set email alerts
|

Mouse skin passage of Streptococcus pyogenes results in increased streptokinase expression and activity

Abstract: The plasminogen activator streptokinase has been proposed to be a key component of a complex mechanism that promotes skin invasion by Streptococcus pyogenes. This study was designed to compare ska gene message and protein levels in wild-type M1 serotype isolate 1881 and a more invasive variant recovered from the spleen of a lethally infected mouse. M1 isolates selected for invasiveness demonstrated enhanced levels of active plasminogen activator activity in culture. This effect was due to a combination of incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…Western immunoblotting experiments using anti-SpeB polyclonal sera demonstrated that the cysteine protease SpeB, which is known to degrade streptokinase (33) was not present in supernatants harvested at this phase of growth (data not shown). This was corroborated by Western-immunoblotting performed using anti-streptokinase polyclonal sera as it detected an immunoreactive band ranging from approximately 46 to 49 kDa in culture supernatants for all GAS isolates, including those harbouring a cluster 2 ska allele ( Figure 2B).…”
Section: Activity and Expression Of Streptokinase Allelic Variantsmentioning
confidence: 98%
“…Western immunoblotting experiments using anti-SpeB polyclonal sera demonstrated that the cysteine protease SpeB, which is known to degrade streptokinase (33) was not present in supernatants harvested at this phase of growth (data not shown). This was corroborated by Western-immunoblotting performed using anti-streptokinase polyclonal sera as it detected an immunoreactive band ranging from approximately 46 to 49 kDa in culture supernatants for all GAS isolates, including those harbouring a cluster 2 ska allele ( Figure 2B).…”
Section: Activity and Expression Of Streptokinase Allelic Variantsmentioning
confidence: 98%
“…Accordingly, we investigated the functional effect of CovS on SK2b production in AP53 cells through examination of the activation of hPg by dialyzed whole cell culture supernatants of mid-log phase (A 600 nm ϳ0.6) GAS cells. E64 (28 M) was maintained in the inoculated cultures and in assays to inhibit the known degradation of SK by aSpeB (47). The data obtained show that AP53 cells mutated to display the WT-CovRS system, viz.…”
Section: Effect Of the Truncation Mutant Of Covs (Covs M ) On Functiomentioning
confidence: 99%
“…SpeB is known to cleave host proteins including extracellular matrix components, cytokine precursors, immunoglobulins and antimicrobial peptides (1,6,7), and has been shown to play an important role in establishing localized skin infections (8). SpeB also degrades GAS virulence factors including the cell wall-associated fibrinogen-binding anti-phagocytic M1 protein (9,10), various superantigens (11,12), and the secreted plasminogen activator streptokinase (13).…”
Section: Epidemic Invasive Group a Streptococcus (Gas S Pyogenes) Dmentioning
confidence: 99%